Answer:
The solution of given equation is ( - 1 + 2 i ) , ( - 1 - 2 i )
Step-by-step explanation:
Given equation as :
3 x² + 6 x +15 = 0
The value of x fro the quadratic equation a x² + b x + c = 0 is obtained as
x =
So , from given eq , the value of x is now obtain as
x =
Or, x =
Or, x =
∴ x = ( - 1 + 2 i ) , ( - 1 - 2 i )
Hence The solution of given equation is ( - 1 + 2 i ) , ( - 1 - 2 i ) Answer
Answer:
they can??!!!
Step-by-step explanation:
omigod wowoow
Answer:
14
Step-by-step explanation:
Replace with the values
15-1/2(2) = 15-1 = 14
Answer:
9 ounces
Step-by-step explanation:
Answer:
$73.60
Step-by-step explanation:
Original price: $64
Markup: 0.15($64) = $9.60
New retail price: $64 + $9.60 = $73.60